Ingarden’s Criticism of Husserl’s Transcendental Idealism - Sodeika, Tomas (Problemos, 1980)
The present paper considers Ingarden’s criticism of Husserl from the point of view of the structure of philosophical theory. In his criticism of Husserl’s transcendental idealism Ingarden is found to reveal considerable contradictions in Husserl’s conception. However a number of Ingarden’s propositions (as, for instance, the treatment of the subjective sense in contrast to objective being, the distribution of philosophy into several unrelated philosophical disciplines, and the identification of the cognizing object with the passive observer) testifies to Husserl’s disregard of certain aspects of the dialectics typical for transcendentalism, his criticism tends to acquire a character of a pre-Kantian philosophical theory.